Ethics, Social Economy and Integral Development (2006)
Expressing concern about every dimension of human welfare, this paper explores the possibility of enhancing integral development by means of potential synergetic connections between ethics and the postulates of social economy. Arguments about the importance of utopian and ethical thinking precede the case for a more comprehensive approach towards human development. The synergetic relationship among social economy, ethics, and integral development is based on the simultaneous articulation of ethical definitions, literature from the field of social economy, and the ideas of the philosopher Ken Wilber. The article concludes with an exhortation to learn from the social economy as an inspiring mean to strive for the implementation of the ideals of ethics and integral development. Even though utopian, the big gap that separates us from a ‘better world’, makes compulsory the quest for virtuous paths.